Seismic performance of a nonlinear energy sink with negative stiffness and sliding friction. Issue 11 (14th August 2019) - Chen, Yangyang; Qian, Zhichao; Chen, Kai; Tan, Ping; Tesfamariam, Solomon
Summary: In this paper, to enhance passive targeted energy transfer, a novel nonlinear energy sink (NES) system is developed. The NES system integrates negative stiffness obtained through geometrical nonlinearities, friction, and sliding mass. Considering a one‐story shear frame, governing equations of the NES system are developed and substantiated through experimental work. The governing equations of the system were subsequently used to select the optimal design parameters. The experimental results validate the numerical predictions that a significant fraction of energy introduced directly to the primary structure by seismic excitation is transferred to the present NES and dissipated. The seismic performance of the present NES is compared with those of the linear tuned mass damper and the cubic NES. The comparison shows that the attenuation observed under the present NES control is competitive and is robust with respect to variation of the primary structural stiffness. Numerically, further sensitivity analysis was carried out to investigate the effect of peak ground acceleration values and stiffness ratio.